Prognostic impact of the lymph node metastatic ratio on 5-year survival of patients with rectal cancer not submitted to preoperative chemoradiation - Jacomo,Alfredo Luiz (2011)
Lymph node metastases are a major prognostic factor in colorectal cancer. Inadequate lymph node resection is related to shorter survival. The lymph nodes ratio (LNR) has been used as a prognostic factor in patients with colon cancer. Few studies have evaluated the impact of LNR on the 5-year survival of patients with rectal cancer. OBJECTIVE: To evaluate the impact of LNR on the survival of patients with rectal cancer not submitted to preoperative chemoradiotherapy. METHODS: Ninety patients with rectal cancer excluding colon tumors, synchronous tumors, hereditary colorectal cancer and those undergoing preoperative chemoradiation. The patients were divided into three groups according t < 0.05). RESULTS: The 5-year survival was related to the Dukes classification, TNM, number of metastatic lymph nodes and LNR. A difference was observed in 5-year survival between the different classes of LNR. Patients classified as LNR-0 had a survival rate of 85%, while classes LNR-1 and LNR-2, 73 and 19%, respectively (p=0.0001). CONCLUSIONS: The results showed that the LNR has an impact on 5-year survival of patients with rectal cancer not submitted to neoadjuvant therapy.